2006
DOI: 10.1590/s0100-06832006000100014
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos de sistemas de preparo nas propriedades físicas de um Latossolo Vermelho distrófico

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
45

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 31 publications
(43 reference statements)
3
14
0
45
Order By: Relevance
“…These Db c values were similar to those reported by Müller (2002) in a Red Nitossol (Haplortox) with 590 g cm -3 clay in the 10-20 cm layer (Db c = 1.33 g cm -3 ), and higher than the 1.28 g cm -3 Db c reported by Tormena et al (1998) in a Red Latossol with 800 g cm -3 clay in the 0 to 10 cm layer. Cavalieri et al (2006) observed critical Db in treatments with mechanical management, decreasing the percentage of samples with Db > Db c . For Klein & Câmara (2007), sporadic sub-soiling in areas under no tillage result in favorable soil physical conditions for plant development, specifically by reducing the soil penetration resistance.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…These Db c values were similar to those reported by Müller (2002) in a Red Nitossol (Haplortox) with 590 g cm -3 clay in the 10-20 cm layer (Db c = 1.33 g cm -3 ), and higher than the 1.28 g cm -3 Db c reported by Tormena et al (1998) in a Red Latossol with 800 g cm -3 clay in the 0 to 10 cm layer. Cavalieri et al (2006) observed critical Db in treatments with mechanical management, decreasing the percentage of samples with Db > Db c . For Klein & Câmara (2007), sporadic sub-soiling in areas under no tillage result in favorable soil physical conditions for plant development, specifically by reducing the soil penetration resistance.…”
Section: Resultsmentioning
confidence: 81%
“…According to Carter et al (1999), the LLWR in NT is lower than in conventional tillage because SR reaches 2.0 MPa at higher moisture contents in the former system, due to the higher Db usually found in the conservation system. Betz et al (1998) and Cavalieri et al (2006) also observed greater LLWR in soil under conventional tillage and chiseling, resulting in a favorable physical environment for root growth. Regardless of soil depth, the water content bringing SR to 2 MPa (θ RP ) equaled the lower LLWR limit in all samples, and was higher than θPWP irrespective of Db in the first year.…”
Section: Resultsmentioning
confidence: 94%
“…Já Tormena et al (1998) obtiveram Dsc de 1,28 kg dm -3 , em Latossolo Vermelho, com 800 kg dm -3 de argila na camada de 0 a 10 cm. Cavalieri et al (2006) também observaram maior Dsc em tratamentos, envolvendo solos manejados mecanicamente, reduzindo-se a probabilidade de ocorrência de amostras com densidades superiores à Dsc.…”
Section: Densidade Crítica (Dsc)unclassified
“…Alguns autores comprovaram a influência do manejo da cobertura do solo no armazenamento e na disponibilidade de água para as plantas em solos derivados do arenito Caiuá (Cavalieri et al, 2006;Fidalski & Tormena, 2007;Fidalski et al, 2008;2010a,b). Em 2010, cogitou-se a hipótese de que a retenção e disponibilidade de água desses solos fossem dependentes do seu material de origem, pois essa característica não era considerada como fator limitante para reter água desses solos para a produção agrícola.…”
Section: Introductionunclassified